Twice upon a Time : Selected Stories, 1898-1939 - Montgomery, L. M. (Lucy Maud), 1874-1942 (Book collections on Project MUSE., 2022)
"This collection of short stories by L.M. Montgomery reveals the early workings of parts of Anne of Green Gables, its sequels, and her other ever-popular novels."--